A cross-sectional study of metabolic and endocrine complications in beta-thalassemia major - Najafipour, Farzad (Ann Saudi Med, 2008)
BACKGROUND AND OBJECTIVES: Iron overload is a major problem in patients with beta-thalassemia major, and it has many structural and metabolic consequences. The aim of this study was evaluation of endocrine disturbances in patients with beta-thalassemia major who were older than 10 years of age. PATIENTS AND METHODS: In this cross-sectional study, investigators collected demographic data and medical histories, as well as menstrual history in females, from the medical records of 56 patients with beta-thalassemia major. Patients were examined to determine their pubertal status and the standard deviation score for height for evaluation of short stature. For evaluation of glucose tolerance, a fasting blood glucose and oral glucose tolerance test were performed. Evidence for diabetes mellitus was based on American Diabetes Association and World Health Organization criteria. Serum levels of calcium, phosphorous, thyroid-stimulating hormone, free thyroxin, luteinizing hormone and follicular-stimulating hormone, and estradiol in girls and testosterone in boys were measured. RESULTS: The mean and standard deviation for age in the 56 patients (36 males and 20 females) was 15.62±4.44 years. Diabetes mellitus was present in 5 patients (8.9%), impaired fasting glucose was found in 16 patients (28.6%) and an impaired glucose tolerance test was found in 4 patients (7.1%). Short stature (standard deviation score <−2) was seen in 25 (70%) boys and 14 (73%) girls. Impaired puberty was found in 40 patients (71%). Hypocalcaemia and primary overt hypothyroidism were present in 23 (41%) and 9 patients (16%), respectively. Only eight patients (14.3%) had no endocrine abnormalities. CONCLUSION: Despite therapy with deferoxamine to treat iron overload, the risk of secondary endocrine dysfunction remained high. Hypogonadism was one of the most frequent endocrine complications. Impaired glucose tolerance, short stature, hypocalcemia, subclinical and overt hypothyroidism are also frequent.